Pertumbuhan Tanaman dan Indikator Keberhasilan Revegetasi di Areal Pasca Tambang Batubara PT Kitadin Site Embalut Provinsi Kalimantan Timur: Plant Growth and Indicator of Revegetation Success in Post-Coal Mining Area of PT Kitadin Site Embalut, East Kalimantan Province - Rahayu, Rimba Novita; Sri, Sarminah; Sigit, Hardwinarto (HUTAN TROPIKA, 2024)
Research on revegetation was carried out in the post-coal mining area of ​​PT Kitadin Site Embalut, East Kalimantan province. The objective of this research is to know the revegetation activities, plant growth and their success levels through the references of revegetation success indicators. The selection of research plots by using purposive sampling on revegetation area in planting blocks for the 2013, 2015 and 2017 years. In each planting block contains 3 plots and every plot was 40 m x 25 m. The results of this research show that the plant growth from 7 years old (2017) to 9 years old (2015) is relatively faster when compared to from 9 years old (2015) to 11 years old (2013). Most of the revegetation activities in all plots met the good category, but for the composition of plant species, namely the trees number of pioneer and local plants in all plots, also the percentage of plant growth in plots for the 2017 year, there needs to be an increase in achievement to the good category. This increase is through planting activities by increasing the tress number of pioneer and local plants in all plots, also maintenance activities in plots for the 2017 year.